التجدّد الطبيعي في محمية جبّاتا الخشب والعوامل المؤثرة فيه - نادر, سهيل; رضوان, زهراء (Latakia University Journal -Biological Sciences Series, 2013)
يعدّ تجدّد الغابات ضرورةً مهمةً وملحّة في كافة مناطق وجودها، وذلك لحماية البيئة وتدعيم التّنوع الحيوي. لذلك كان هدف البحث دراسة أهم العوامل المؤثرة في التجدّد الطبيعي في غابة جباتا الخشب، واقتراح ما يلزم للوصول بهذه التجمعات نحو الأوج وتحديد معوقات ذلك، إضافةً إلى وضع الخطط المناسبة لحمايةِ وتطويرِ هذه المنطقة. ولتحقيق هذا الهدف أجريت عدة كشوف نباتية ما بين أيار2010 وآذار2011، تمّت من خلالها متابعة عملية التجدّد الطبيعي لمختلف الأنواع النباتية في المحمية ولا سيّما النباتات الشجرية منها كأشجار السنديان بنوعيه والزعرور والبطم والوزال وغيرها. لقد أظهرت هذه الدّراسة ضعفاً كبيراً جداً في التجدّد الطبيعي للسنديان بشكلٍ عام ومرافقيه من الأشجار بشكلٍ خاص، وقد تبيّن أنّ الدور البارز في ذلك يعود للعوامل غير الطبيعية ولا سيّما السياحة البيئية والنشاطات البشرية المتنوعة. فقد أوضحَت الدراسة أنّ النّشاط البشري المتنوع في المنطقة رغم إعلانها كمحمية، هو المعرقل لا بل المانع أمام التّجدد، الشيء الذي كان له الأثر الواضح في تراجع تجدّد الأنواع النباتية وانخفاض أعداد أفرادها، سواء كانت عشبية أم شجرية، نتيجة الرّعي الجائر والوطء الشديد وعمليّات الجمع العشوائي للنّباتات الطبّيّة والغذائيّة، إضافةً إلى إشعال النّار في الغابة ونشاطات المتنزهين وغيرها من العوامل. Forests regeneration is considered as an important and urgent need in all their existence areas for protecting environment and supporting biodiversity. Accordingly, the research aims to study the most important influencial factors in natural regeneration in Jabatta Al Khashab wood reserve and recommend requirements for promoting these societies to an apogee, define the hindering obstacles, and to set adequate plans to protect and develop this area. For realizing this goal, several botanic field inspections (Relevés) were performed through the time span lasted from May 2010 March 2011, through which, natural regeneration process of different botanic species was followed up in the reserve, in particular woody flora such as both oak species trees (Quercus sp), neapolitan (Crataegus azarolus) terebinth, broom and others. The research revealed a very weak natural regeneration of oaks (Quercus sp) in general and its attendant tree in particular. It was realized that major role in that is attributed to unnatural factors namely environmental tourism and diversified human activities. The research revealed that diversified human activity in the area, though declaring it as a natural reserve, is not only the regeneration hinderer but even the regeneration inhibitor. This activity has an explicit impact on botanic grassy and woody species regeneration decline and species population retreat due to overgrazing, overloading, random harvesting of nourishing and herbal plants, fire lighting in the reserve, picnickers' activities, and other factors.